THE DEVELOPMENT OF THE CONCEPT OF CONSTITUTIONAL DAMAGES (The Pretoria Student Law Review, 2021)
Any question dealing with the development of law requires, by its very nature, a discussion of sometimes factually distinguishable but legally interwoven points; thus focus is placed on the law of constitutional damages. Every effort is made to present cases in a manner that solidifies an argument of progress and refinement in relation to the concept of constitutional damages as a remedy. The anchor of this work is the Constitution. Fose,  the locus classicus on constitutional damages, introduces the notion of constitutional damages as a remedy in South African litigation and is threaded throughout this work. Strong reliance is placed, inter alia, on the decisions of Kate, Modderklip,  Dikoko, and Mboweni. The thrust of my argument is that the remedy of constitutional damages should only be relied upon when most appropriate and practical to ensure the vindication of constitutional rights in light of the facts of a particular case and alternative legal remedies.
Keywords: development of law; constitutional damages; the Constitution; litigation; alternative legal remedies